The doctor in a vise between health and the law: What to do? - Murat Akbaba; Vedat Davutoğlu (KARE Publishing, 2016)
The relationship between patients and physicians has maintained its importance throughout human history because of special features of the medical profession. This relationship engendered true loyalty of patients to their physicians as well as serious legal conflicts. Medical malpractice has gained importance among physicians and ignited discussion because of new articles added to the Turkish Penal Code in 2005. In a very short time, the penalties mandated had a chilling, negative effect on doctors, resulting in loss of affection for the profession, hesitation to intervene, and burnout syndrome. Cardiologists work in an environment where the line between life and death is very thin. The aim of the present study was to raise awareness and avoid possible grievances by informing them of their responsibilities under the law.